Risk Taking Behavior Among College Students and Factors Affecting this Behavior - Fırat, Sunay; Yoldaşcan, Elçin; Çot, Duygu Ayabakan; Dağlıoğlu, Nebile; Gülmen, Mete Korkut (The Bulletin of Legal Medicine, 2016)
Objective: Risky health behaviors are usually acquired during adolescence, but their effects are reflected in adulthood, causing significant increases in mortality and morbidity rates. This study aims to examine risky behaviors among college students concerning the use of tobacco, alcohol and addictive substances, sexuality, personal safety, and violence. Materials and Methods: This is a descriptive study conducted in the main campus of Çukurova University in November and December 2015. After receiving written approval, an “Information Form” designed to collect demographic data and the “Risky Behaviors Scale - College Form” were administered to college students. The risky behaviors scale is a 60-item Likert-type scale. It consists of seven sections: antisocial behavior, use of alcohol, use of tobacco, substance use, nutritional habits, suicidal tendency, and dropping out of school. Higher scores for each of these sections indicate higher risk. The data were analyzed using the software package SPSS 20. Results: Of the 184 students participating in the study, 105 (57%) were female and 79 (42,9%) were male. The average age of the participants was 20,21±1,91 (min:18, max: 39). Male students having university education had higher scores for antisocial behavior, use of tobacco, substance use, and dropping out of school, compared to female students having university education, and these differences were statistically significant (p≤0,05). Students living with housemates had higher scores alcohol use compared to students living with their families or in dormitories, and for tobacco use compared to students living with their families (p≤0,05). Conclusion: This study found that gender and living arrangements are significant determinants of risky behavior. In Turkey, living with one’s parents is common, due to various reasons including customs, and young people living away from their parents are influenced by one another. More activities should be undertaken to protect young people from risky behaviors in college environments, which they share with many other students, and to help them acquire the necessary life skills to avoid risky behaviors. In conclusion, counseling units should be established in colleges to understand and prevent risky behaviors among young people in the future, and training sessions and group sessions should be conducted by experts in these units to provide proper guidance to students.